IMPACT OF PROFIT-LOSS SHARING FINANCING ON POVERTY ALLEVIATION OF SHRIMP FARMERS IN TULANG BAWANG REGENCY (CASE STUDY: KEMITRAAN BUMIDIPA) - Shofiyanto, Shofiyanto; Findi, Muhammad; Ayyubi, Salahuddin El (Jurnal Ekonomi & Studi Pembangunan, 2017)
This research aimed to describe the core values of Kemitraan Bumidipa as sharia microfinance program that applies profit-loss sharing scheme, to elaborate the main obstacles that might cause the failure of the program, to analyze the effectivity of its financing, and to analyze the impact of financing on poverty alleviation of shrimp farmers in Rawajitu Timur District, Tulang Bawang Regency. Descriptive analysis, qualitative analysis and poverty indices are used as the analysis methods. The result shows that, on the one hand, the core values of Kemitraan Bumidipa are the real profit sharing system, professional financial services, and the investment guarantee model for its financing. On the other hand, the risks faced by the program are the the unstable environment of shrimp farming, technical problems, the shrimp’s price fluctuation, and moral hazard behavior. According to effectivity analysis, overall this program has been effective. Based on poverty indices result, sen index of farmers increase after becoming members of Kemitraan Bumidipa as the result of the failure of farmers’ cultivation. As recommendation, it should be a supervision mechanism to prevent the members from moral hazard act and it’s neccessary for further research particularly related to the unstable environment of shrimp farming and the fluctuation of shrimp’s price.